Computer-Based National Assessment An Effort to Improving Education Quality - Ritman Hendra; Adripen Adripen; Moch. Hafid; Nur Aini Parwitasari; Megie Ambarsari (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to provide an understanding of computer-based national assessments to improve the quality of education. The method used in this research is qualitative in the literature study approach. In processing and retrieving data and documentation through books, journals, and other relevant studies, a descriptive analysis narrative is developed, and finally, conclusions are drawn. Based on Permendikbudristek number 17 of 2021, the implementation of a national assessment by looking at the various inequalities that occur in educational institutions, both from the elements of leadership, resources, and students, as well as other factors that add to the series of problems. A national assessment that the government realized started in 2021 as an effort to restore the quality of education. As steps carried out by the Ministry of Education and Technology through three stages of assessment for both leaders of educational institutions, teachers, and students, namely first, minimum competency assessment (AKM), which includes literacy and numeracy. Second, the character survey, and third, the study environment survey. A national assessment can provide information on the development of education sustainably so that, in the end, education in each educational institution is evenly distributed and quality.